Enhancing Okra Productivity Through Seed Priming: Insights from Chitwan, Nepal - Mandeep Thapa; Basanta Kumar Rimal; Sujan Lamichhane; Arjun Kumar Shrestha (Turkish Journal of Agriculture: Food Science and Technology)
Seed hardiness threatens the growth and yield of okra by causing low and non-uniform germination. Seed priming is an effective, ecologically sound, and practical technique to promote germination. A study was conducted from March to July 2024 in Chitwan, Nepal, to evaluate the effectiveness of different seed priming treatments in enhancing the germination, growth, and yield of okra. The study used a randomized complete block design (RCBD) with four replications, under five different treatments: Control: no soaking, Hydro priming, NaCl @ 0.5%, KNO3 @ 0.5%, GA3 @ 100 ppm. Each plot consisted of twenty plants. Data on germination percentage, growth, and yield were recorded using standard methods. The collected data were examined employing MS Excel and R-studio version 4.3.2. Seeds primed with GA3 @ 100 ppm showed a significant rise in germination percentage (90 %), plant height at 30 DAS (17.50 cm) and 45 DAS (39.81 cm), leaf canopy diameter at 45 DAS (69.68 cm), fruit number per plant (9.15), fruit weight per plot (423.75 g), and maximum yield (1.41 t/ha), followed by other treatments. The leaf number per plant and fruit length were not significant. However, priming positively affected germination, growth, and yield parameters compared with the control (no soaking). The study found that priming okra with GA3 @ 100 ppm enhanced growth and yield. Seed priming with GA3 is recommended for okra production in Rampur, Chitwan.